Narrative triggers of information sensitivity - Kim Ristolainen (Aboa Centre for Economics (ACE), 2022)
Economic research has shown that debt markets have an information sensitivity property that allows these markets to work properly when price discovery is absent and opaqueness is maintained. Dang, Gorton and Holmström (2015) argue that sufficiently 'bad news' can switch debt to become information sensitive and start a financial crisis. We identify narrative triggers in the news by utilizing machine learning methods and daily information about firm default probability, the public's information acquisition and newspaper articles. We find state-specific generalizable triggers whose effect is determined by the language used by journalists. This language is associated with different psychological thinking processes.
Keywords: G01; G14; G41; 330; information sensitivity; debt markets; financial crisis; machine learning; news data; primordial thinking process